Psychological Health in Respect of Self Esteem among Rural, Urban and Semi Urban College Students of Different Genders of East Midnapore District: A Cross Sectional Study (Indian Journal of Public Health Research & Development, 2020)
Self esteem is the expression of the existence of psychological health. Self esteem is needed as it is one of themost important human rights. Self esteem is greatly affects the quality of life as well as the productivity ofthe people that is why the self esteem is greatly impacted on the student’s performance as they are the futureof our country. This study has conducted to assess the existing level of self esteem among east Midnaporecollege students of technical and allied stream; also it is concentrated on whether self esteem is significantlyrelated with gender of the students and area the students are residing. Total 159 students are included in thestudy after doing convenient sampling method. A questionnaire has formed which follows Rosenberg SelfEsteem scale system. T test and ANOVA has conducted by SPSS 21 software and it shows neither gendernor area are significantly related with the level of self esteem among students of technical and allied streambecause in every cases the p value is greater than .05.
Keywords: Psychological health, Self esteem, rural, semi urban, urban, mental health, human right, technical and allied.